2023
DOI: 10.1002/advs.202305042
|View full text |Cite
|
Sign up to set email alerts
|

Unloading‐Induced Skeletal Interoception Alters Hypothalamic Signaling to Promote Bone Loss and Fat Metabolism

Qiaoyue Guo,
Ningrong Chen,
Kalp Patel
et al.

Abstract: Microgravity is the primary factor that affects human physiology in spaceflight, particularly bone loss and disturbances of the central nervous system. However, little is known about the cellular and molecular mechanisms of these effects. Here, it is reported that in mice hindlimb unloading stimulates expression of neuropeptide Y (NPY) and tyrosine hydroxylase (TH) in the hypothalamus, resulting in bone loss and altered fat metabolism. Enhanced expression of TH and NPY in the hypothalamus occurs downstream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Bone mass and cortical bone of the talus decreased significantly in HU mice while body weight remained unchanged over time relative to their grounded littermate controls (Fig. 1e ) 41 . Again, the number of osteoblasts in the talus decreased significantly in the HU mice compared to the controls (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Bone mass and cortical bone of the talus decreased significantly in HU mice while body weight remained unchanged over time relative to their grounded littermate controls (Fig. 1e ) 41 . Again, the number of osteoblasts in the talus decreased significantly in the HU mice compared to the controls (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…HU Animal Model: For HU model after unilateral femoral fracture, suspending the hind limbs mimicked the microgravity or disuse conditions as previously reported 5 , 52 , 53 . One day after fracture modeling, 8 - to 10-week-old male (age-matched) genotype-matched mice were randomly separated into HU or ground controls.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 160-190 million new bone fractures occur each year, and despite advances in surgical treatments, 5-10% of patients suffer from impaired healing 1 , 2 . Decreased loading stimuli, e.g., lack of mechanical loading in the setting of prolonged bed rest and paralysis, result in reduced bone healing capacity, leading to delayed fusion or nonunion 3 - 5 . However, the underlying mechanism of mechanical stimuli regulating the fracture healing remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, prostaglandin transporter gene SLCO2A1 was shown to undergo significant downregulation in HUVEC and EA.hy926 cells exposed to clinostat-simulated microgravity [57], while PGE 2 has been suggested as an important player in the molecular mechanisms behind microgravity-induced modifications. Indeed, Guo and colleagues have recently reported that PGE 2 is secreted by osteoblasts under mechanical loading, or in conditions of low bone density, and controls bone density and fat metabolism by triggering hypothalamic expression of tyrosine hydroxylase (TH) and of neuropeptide Y (NPY) through the EP4-expressing sensory nerves of ascending interoceptive pathways [58][59][60]. With regard to this, the authors have shown that hindlimb suspension leads to PGE2/EP4-mediated signaling in sensory interoceptive pathways, which leads to bone loss and adipose tissue lipolysis [60] Apparently, microgravity also acts by altering membrane balance and ion permeability through the function of Ca 2+ channels [61,62].…”
Section: Eicosanoids In Microgravitymentioning
confidence: 99%